PELANGGARAN AKAD MUZARAAH DALAM PENGELOLAAN TANAH SAWAH SEBAGAI OBJEK GADAI: (Studi Kasus di Kemukiman Gampong Lhang Kecamatan Pidie) - Muhammad, Muhammad; Fansurna, Silvia; Amri, Amri (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2024)
This research discusses the violation of the muzaraah contract in the management of paddy fields as an object of pawn case study in Pidie District. The problems are the practice of muzara'ah in the management of paddy fields in the Gampong Lhang settlement and the factors for violating the muzara'ah contract in the Gampong Lhang settlement and the views of Islamic law on violations of the muzara'ah contract in the management of paddy fields in Pidie District. The research used descriptive analysis method and through a qualitative approach and through obtaining data from library research and field research with data collection techniques through observation, interviews and documentation. The results showed that the practice of violations in the muzaraah contract occurred due to the misuse of paddy fields which were then mortgaged by the manager, which of course was done without the permission of the landowner. The factors causing the violation of the muzaraah contract were caused by the manager's lack of responsibility for the agreed contract, so the manager gave the reason that this happened because of economic difficulties so that it was necessary to mortgage the rice fields. According to Islamic law, the muzaraah that was carried out caused a violation of the contract, in Islam it is not permissible to mortgage to another party the object of muzaraah.